Trends and impact of government prevention policies on pulmonary tuberculosis notification and mortality in Ningbo, China (2004–2021) - He, Tianfeng; Lin, Lin; Qian, Xujun; Yao, Weitao; Li, Guoxing; Huang, Jing (Frontiers in Tuberculosis, 2025)
BackgroundTuberculosis (TB) is a major global health threat, with Ningbo reporting over 3,000 annual cases of pulmonary tuberculosis (PTB). This study analyzes the notification and mortality rates of PTB in Ningbo from 2004 to 2021.MethodsWe calculated age-standardized annual notification and mortality rates for PTB per 100,000 population and employed interrupted time series regression to evaluate the impact of government policies on these rates.ResultsFrom 2004 to 2021, Ningbo recorded 68,392 PTB cases and 236 deaths. The unstandardized notification and mortality rates were 51.31 and 0.18 per 100,000 population, respectively. Joinpoint trend analysis showed a significant decline in PTB notification from 2007 to 2016 (APC = −7.3%, P < 0.05). Although mortality decreased from 2017 to 2021, this reduction was not statistically significant (APC = −20.5%, P = 0.106). Interrupted time series analysis indicated that government policies led to an estimated reduction of three cases in age-standardized PTB notification and about 0.025 deaths per 100,000 population.ConclusionBetween 2004 and 2021, Ningbo saw a notable decrease in both the notification and mortality rates of PTB due to effective control measures. To achieve the End TB Strategy targets for 2035, it is crucial to enhance efforts in diagnosing and treating PTB—especially among males, adolescents, and older adults.